PENGARUH METODE PEMBELAJARAN SCRAMBLE GAME TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH IBTIDAIYAH MUHAMMADIYAH 06 BRONDONG LAMONGAN - Suci Windriyani; Idzi layyinnati (Jurnal Mahasiswa Pendidikan, 2023)
Education plays a crucial role in human life. In the learning process, a teacher's understanding of the mastery of the teaching methods they use is essential. Therefore, the researcher uses the scramble game learning method to be applied at Muhammadiyah 06 Brondong elementary school in the subject of Akidah Akhlak, as this learning method is considered suitable for implementation in the fifth grade of Muhammadiyah 06 Brondong elementary school. Based on the results of the validity test calculations. Based on the results of the validity test calculations, it shows that 20 multiple-choice questions are considered valid, meaning that rhitung > rtabel, where the rtabel value is 0.455. Next is the reliability calculation using Cronbach's alpha, with a calculated r value from the pre-test of 0.880 and a post test of 0.897. The tested data is considered reliable because the calculated r value is greater than 0.06, meaning it meets the reliability requirements of Cronbach's alpha. Normality test, the researcher here used the Shapiro-Wilk technique because the number of respondents obtained is < 50, with the values obtained for the pre test being 0.251 and for the post-test being 0.134, both of which are > 0.05, which is the requirement for the data to be considered normal. The next calculation is homogeneity; data is said to be homogeneous if ftabel > fhitung. The value of ftabel obtained is (0.221) and rhitung. (0,126). Based on the results of the product moment correlation test, the calculated r value is 0.622 and the table r value is 0.455. This indicates that the calculated r is greater than the table r, leading to the conclusion that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This means there is an influence of the Scramble Game method on the learning outcomes in the subject of Akidah Akhlak for fifth grade at MIM 06 Brondong. A correlation coefficient of 0.622 falls between 0.60 and 0.799, thus it is categorized as moderate. In the significance test results, a t-value of 3.274 was obtained, while the t-table value with 19 respondents at a significance level of α=0.05 and degrees of freedom (df) = n-2 is 2.271. It can be concluded that if t calculated > t table, then Ho is rejected and Ha is accepted, meaning that the pretest and posttest data are significant.